2D Metal Carbides and Nitrides (MXenes) Structure, Properties and Applications - Anasori, Babak; Gogotsi, Yury.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes the rapidly expanding field of two-dimensional (2D) transition metal carbides and nitrides (MXenes). It covers fundamental knowledge on synthesis, structure, and properties of these new materials, and a description of their processing, scale-up and emerging applications. The ways in which the quickly expanding family of MXenes can outperform other novel nanomaterials in a variety of applications, spanning from energy storage and conversion to electronics; from water science to transportation; and in defense and medical applications, are discussed in detail. .
Introduction -- Structure and Synthesis -- Processing -- Properties -- Applications.
Keywords: Materials; Catalysis; Force and energy; Nanochemistry; Energy storage; Materials -- Analysis; Nanotechnology; Materials for Energy and Catalysis; Nanochemistry; Mechanical and Thermal Energy Storage; Characterization and Analytical Technique; Nanotechnology